Interleaved Susceptibility-Weighted and FLAIR MRI for Imaging Lesion-Penetrating Veins in Multiple Sclerosis - Gabr, Refaat E. (Magn Reson Med, 2018)
PURPOSE: To simultaneously image brain lesions and veins in multiple sclerosis. METHODS: An interleaved sequence was developed to simultaneously acquire 3D T2*-weighted (or susceptibility-weighted, SW) and fluid-attenuated inversion recovery (FLAIR) images on a 3.0T MRI system. The pulse sequence parameters were calculated to minimize signal perturbation from steady state while maintaining acceptable image contrast and scan time. Fifteen multiple sclerosis patients were enrolled in this prospective study and underwent a standard MS imaging protocol. In addition, SW and FLAIR images were acquired separately and also in an interleaved manner. The SW and FLAIR images were combined into one image to visualize lesions and penetrating veins. The contrast ratios between white matter lesions and penetrating veins were compared between the interleaved sequence and the individual non-interleaved acquisitions. RESULTS: Interleaved scanning of the FLAIR and the SW pulse sequences was achieved, producing aligned images, and with similar image contrast as in the non-interleaved images. A total of 1076 lesions were identified in all patients on the combined SW-FLAIR image, of which 968 lesions (90%) had visible penetrating veins. Lesion-to-vein contrast ratio was 32.7 ± 17.9 (mean ± standard deviation) for the interleaved sequence compared to 28.1 ± 13.7 using the separate acquisitions (P<0.001). CONCLUSION: The feasibility of interleaved acquisition of susceptibility-weighted and FLAIR images was demonstrated. This sequence provides self-registered images and facilitates the visualization of veins in brain lesions.